Communicative Language Teaching Techniques and Learning Styles on The Student’s Speaking Skill at Private Vocational School - irfan hadi (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
The purpose of the research is to know the effect of Teaching techniques; Role Play, Information Gap and Learning style; Right Brain Dominant and Left Brain Dominant toward student’s Speaking Skill at Private Vocational School in South Jakarta. To collect the data, the writer persuades two techniques in teaching English speaking skill and learning style to know the characteristics of the students in learning. To improve the quality of teaching and learning process the writer uses an appropriate material with the curriculum and the syllabus. The method used in this research is experiment method. The data got by the writer by giving a Speaking Skill exercise and also a questionnaire. After analyzing the data, some conclusions about the effect of role play, information gap technique and learning style have been gotten by the writer. According to ANOVA table, the Sig. Score of teaching technique is 0,000 which is lower than 0,05 (0,000 < 0,05 ) means that the hypothesis works and Ho is rejected. So there is an influence between teaching technique towards speaking skill. The sig. Score of learning style is 0,968 is higher than 0,05 (0,968 > 0,05) means that Ho is accepted. So there is no influence between learning style towards speaking skill. The sig. Score of interaction is 0,562 is higher than 0,05 ( 0,562 > 0,05) means that Ho is accepted. So there is no influence interaction between teaching technique and learning style towards speaking skill